Morphological Variation of Blue Panchax (Aplocheilus panchax) Lives in Different Habitat Assessed Using Truss Morphometric - Mustikasari, Diah; Suryaningsih, Suhestri; Nuryanto, Agus (Biosaintifika: Journal of Biology & Biology Education, 2020)
Blue panchax (Aplocheilus panchax Hamilton, 1822) lives in broad ranges of habitat from open waters to closed waters, including at ex-tin mining pits in Bangka Island, Indonesia. Variable habitats might cause morphological variations due to different ecological factors. This study aimed to assess the morphological variation of blue panchax collected from different habitats using truss morphometric characters. Fish samples (70 individuals) were collected from abandoned ex-tin mining pits of different ages and a river in Bangka Island. Twenty-nine truss characters were analyzed using the Kruskal-Wallis test and post hoc with Dunn’s test . The results showed that almost all of the body parts of blue panchax found in ex-tin mining pits and rivers were significantly different (p-value < 0.05), except some truss characters of caudal peduncle. The post hoc of Dunn’s test showed a positive correlation between habitats and truss characters (adj. sig < 0.05). Some truss characters of killifish were different between ex-tin mining pits with different ages chronosequence, and some other characters were different between pits and river. This study provides the first data about the morphological variation of blue panchax in ex-tin mining pits of different ages. The data is valuable as a scientific basis of further utilization of ex-tin mining pits in the areas.